TINJAUAN TEORITIS KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DARI PERSPEKTIF THEORY OF PLANNED BEHAVIOR - Rahayu Anggraeni; Kristanti Rahman (JURNAL EKONOMI, 2019)
ABSTRACT The aims of this research are to analyze (1) The effect of behavioral belief toward attitude, (2) The effect of normative belief toward subjective norm (3) The effect of control belief toward perceived behavioral control (4) The effect of attitude on taxpayer's intention toward compliance, (5) The effect of subjective norm on taxpayer's intention toward compliance, (6) The effect of perceived behavioral control on taxpayer's intention toward compliance, (7) The effect of taxpayer's intention toward compliance on mediate attitude, subjective norm and perceived behavioral control toward vehicle taxpayer compliance. The hypotheses of this research are: (1) Behavioral belief has a significant effect toward attitude, (2) Normative belief has a significant effect toward subjective norm, (3) Control belief has a significant effect toward perceived behavior control (4) Attitude has a significant effect toward taxpayer's intention toward compliance, (5) Subjective norms has a significant effect toward taxpayer's intention toward compliance, (6) Perceived behavior control has a significant effect on taxpayer's intention toward compliance, (7) Taxpayer's intention toward compilance on mediate attitude, subjective norm and perceived behavioral control has a significant effect toward vehicle taxpayer compliance. Keywords: Behavioral Belief, Normative Belief, Control Belief, Attitude, Subjective Norm, Perceived Behavioral Control, Taxpayer Intention toward Compliance, Motor Vehicle Tax Compliance, Theory of Planned Behavior.